Eksistensi Perempuan Bali Dalam Budaya Patriarki - Desak Made Alit Septiari; I Gusti Ayu Widya Dhammayanti (Pramana: Jurnal Hasil Penelitian, 2023)
Women and their existence are two things that are very closely related. If you look at history, Indonesia has many female figures who contributed to the country's progress, which proves that women are also capable of making changes that are just as significant as men. The struggle for gender equality began with introducing formal education to Indonesian women, as was done by Raden Ayu Adipati Kartini Djojoadhiningrat (Raden Ajeng Kartini). Not only that, Bali also has female figures such as Raden Ajeng Kartini named I Gusti Ayu Rapeg, she and her friends are persistent in visiting people's houses one by one to introduce education for women. The struggle for gender equality fought by female leaders in fact must continue to this day. Many people still underestimate women, especially in areas that adhere to a patriarchal system. This phenomenon is something that must be addressed so that in the future women will have more space to express, create, and feel safe in public spaces.